8th World Congress on Science and Footbal (20-23 May 2015, Copenhagen Denmark, 2015)
ORAL AND POSTER SESSIONS WEDNESDAY, 20 MAY 2015 KP01 - Keynote Plenum S01 - Injuries - Part I S02 - Match analysis - Part I S03 - Testing - Part I S04 - Sport sociology S05 - Injuries - psychological perspectives THURSDAY, 21 MAY 2015 W01 - Fitness training and testing of the top player W02 - Prevention of contact and non-contact injuries in football W03 - Nutrition and supplementation in football S06 - Health - Part I S07 - Health - from a social science perspective S08 - Australian football S09 - Match analysis - Part II S10 - Biomechanics S11 - Fatigue - Part I S12 - General psychology - Part I S13 - Health - psychological perspective S14 - Organization, economics and politics - Part I Poster Session I P01 - Biomechanics, Women & Nutrition and supplementation P02 - Children P03 - Fatigue P04 - Health - prevention, treatment & rehabilitation P05 - Varia - Fatigue, match analysis & injuries KP02 - Keynote Plenum S15 - Coaches - situations and careers - Part I S16 - Career pathways and talent development - Part I Poster Session II P06 - Match analysis - Part I P07 - Injuries P08 - Testing - Part I P09 - Training - Part I S17 - Training - Part I S18 - Children S19 - Rugby S20 - Pedagogical issues S21 - Organization, economics and politics - Part II FRIDAY, 22 MAY 2015 W04 - Australian football rules W05 - Fitness coaching in an elite football team - with special focus on individual-based approach S22 - Injury prevention S23 - A multi-disciplinary examination of football development and performance S24 - Football fans S25 - Environment S26 - Training - Part II S27 - Health - Part II S28 - Match analysis - Part III S29 - Career pathways and talent development - Part II 12:00 - 13:00 S30 - Sport history. Politics and policies - a historical perspective 12:00 - 13:00 Poster Session III P10 - Match analysis - Part II P11 - Testing - Part II P12 - Training - Part II P13 - Varia - Sports medicine KP03 - Keynote Plenum Poster Session IV P14 - Psychological performance issues P15 - Women's football P16 - Psychology P17 - Pedagogical issues, Coaches and team process P18 - Varia - Social science and humanities S31 - Training - Part II S32 - Women's football S33 - Gaelic football S34 - Women's football S35 - Coaches - situations and careers Part II W06 - Association football referee training and performance S36 - Injuries - Part II S37 - Testing - Part II S38 - Career pathways and talent development - Part III S39 - Morality SATURDAY, 23 MAY 2015 S40 - Tactic and technic S41 - Fatigue - Part II S42 - Training - Part III S43 - General psychology - Part II S44 - Migration & integration S45 - Meet the Experts S46 - Health - Part III S47 - General psychology - Part III S48 - Referees and scouts Tom Reilly Memorial Lecture